ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI RESONANSI MEREK PADA KONSUMEN NAILS BYCICA DI YOGYAKARTA - Yogik, Muhamad Azrul; Chresilou, Chresilou (Cahaya Ilmu Bangsa, 2025)
This study aims to provide a deeper understanding of the influence of brand experience, brand awareness, brand attachment, and brand relationship quality on brand resonance. The population in this research consists of customers of the nail salon